Validation of CFD for the Determination of Damping Coefficients for the Use of Wave Energy Converters Modelling - Thilleul, Olivia; Babarit, Aurélien; Drouet, Aurélien; Le Floch, Sébastien (Volume 9: Odd M. Faltinsen Honoring Symposium on Marine Hydrodynamics, 2013)
ASME 2013 32nd International Conference on Ocean, Offshore and Arctic EngineeringVolume 9: Odd M. Faltinsen Honoring Symposium on Marine HydrodynamicsNantes, France, June 9–14, 2013Conference Sponsors: Ocean, Offshore and Arctic Engineering DivisionISBN: 978-0-7918-5543-0 International audience Diffraction-radiation codes enable to model the behaviour of Wave Energy Converters (WEC) and ships seakeeping on several sea-states in a very reasonable computational time. However, the viscous effects are neglected and leads to inaccurate values, mainly at the resonance peak, especially in roll motions for which viscous effects are of major importance. Classically, the viscous effects are represented by adding viscous damping coefficients coming either from experimental data or analytical approach based on numerous approximations. In order to improve the accuracy of the diffraction-radiation solvers, the damping coefficients can also be calculated from Computational Fluid Dynamics (CFD). The first part of the proposed paper presents three experimental test cases to which numerical results are compared. The second part sums up the methodologies to obtain the damping coefficients which can be expressed as drag coefficients in oscillatory flow or as a linear and a quadratic damping coefficient. The numerical parameters to set up models in CFD are then investigated. Time steps, mesh convergence and turbulence models are varied in order to deduce a general methodology to perform damping coefficients computations. The mesh is optimized in terms of results quality and computational time. This optimization is based on the adaptation of the refined zone of the mesh in the wake areas. Three CFD codes are tested: ICARE and ISIS-CFD are developed by Ecole Centrale de Nantes and Star-CCM+ is a commercial code. The final part of the proposed paper is dedicated to the presentation of validation results on the three cases studied, by varying non-dimensional numbers such as Keulegan-Carpenters and Reynolds number. It enables to ...